1778 Del. Acts, Mar. Adjourned Sess. 3-5 - (:unkn) unknown (My University, 1778)
Included " each and every able-bodied, effective, Male white Person between the Ages of Eighteen and Fifty." Militiamen had to provide their own " Musket or Firelock with a Bayonet," plus the cartridge box, cartridges, priming wire, brush, and six flints. For 18-to-20-year-olds who could not afford the mandatory arms, the parents had to provide them, if the parents could afford them.
Keywords: MILITIAS; REQUIRED POSSESSION